Effectiveness and safety of ombitasvir, paritaprevir, ritonavir ± dasabuvir ± ribavirin: An early access programme for Spanish patients with genotype 1/4 chronic hepatitis C virus infection. Issue 3 (15th December 2016) - Perelló, C.; Carrión, J. A.; Ruiz‐Antorán, B.; Crespo, J.; Turnes, J.; Llaneras, J.; Lens, S.; Delgado, M.; García‐Samaniego, J.; García‐Paredes, F.; Fernández, I.; Morillas, R. M.; et al.
Abstract: Over the last 5 years, therapies for hepatitis C virus (HCV) infection have improved significantly, achieving sustained virologic response (SVR) rates of up to 100% in clinical trials in patients with HCV genotype 1. We investigated the effectiveness and safety of ombitasvir/paritaprevir/ritonavir±dasabuvir in an early access programme. This was a retrospective, multicentre, national study that included 291 treatment‐naïve and treatment‐experienced patients with genotype 1 or 4 HCV infection. Most patients (65.3%) were male, and the mean age was 57.5 years. The mean baseline viral load was 6.1 log, 69.8% had HCV 1b genotype, 72.9% had cirrhosis and 34.7% were treatment‐naïve. SVR at 12 weeks posttreatment was 96.2%. Four patients had virological failure (1.4%), one leading to discontinuation. There were no statistical differences in virological response according to genotype or liver fibrosis. Thirty patients experienced serious adverse events (SAEs) (10.3%), leading to discontinuation in six cases. Hepatic decompensation was observed in five patients. Four patients died during treatment or follow‐up, three of them directly related to liver failure. Multivariate analyses showed a decreased probability of achieving SVR associated with baseline albumin, bilirubin and Child‐Pugh score B, and a greater probability of developing SAEs related to age and albumin. This combined therapy was highly effective in clinical practice with an acceptable safety profile and low rates of treatment discontinuation.